If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(X + 2) + -7 = 18 Reorder the terms: 6(2 + X) + -7 = 18 (2 * 6 + X * 6) + -7 = 18 (12 + 6X) + -7 = 18 Reorder the terms: 12 + -7 + 6X = 18 Combine like terms: 12 + -7 = 5 5 + 6X = 18 Solving 5 + 6X = 18 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 6X = 18 + -5 Combine like terms: 5 + -5 = 0 0 + 6X = 18 + -5 6X = 18 + -5 Combine like terms: 18 + -5 = 13 6X = 13 Divide each side by '6'. X = 2.166666667 Simplifying X = 2.166666667
| 0.7t=0.3+0.4t | | 4x-2=9x+1 | | -9x+12+4(3x-3)=7(x-2)-14 | | -6=x/3 | | -11.2+4(2.1+q)=8 | | -5(5x+5)-4+8x= | | -6(-3a-4)= | | -17r=17 | | -5+11x=11x-5 | | -8/3b=5/1 | | 25-x/8=12.5 | | 1/3x+7=14 | | 6y/7-3/8y | | m+5m-5=7 | | 2x+7x-4=95 | | 900/16 | | 6(2x-4)=4 | | (1/3)(x-3)=4-(2x+3) | | 5(1-4x)+x= | | 4+2/5x=4/15x | | 0.45x+0.05(4-x)=0.10(34) | | (128x^8y^12)^(1/6) | | 2.5x+7.8=12.2 | | 5s+36=3s+6 | | 6x+3y+5x=0 | | -16-6x=-4x+12 | | 7x-9=24+7x | | N+2=-14n | | 8y+4(1+y)=3(y-3)+10y | | 2.5x=4.4 | | -3(1+7a)+a= | | -5/6+1/12 |